In Silico, In Vitro and In Vivo Toxicological Assessment of BPP-BrachyNH2, A Vasoactive Proline-Rich Oligopeptide from Brachycephalus ephippium - Arcanjo, Daniel D. R. (2019)
BPP-BrachyNH2 is a proline-rich oligopeptide (PRO) firstly identified in skin secretion of the frog Brachycephalus ephippium, which possess in vitro inhibitory activity of angiotensin-I converting enzyme (ACE) and endothelium-dependent vasorelaxant activity. Considering its potential application in the treatment of cardiovascular diseases, the present work assessed the toxicological profile of the BPP-BrachyNH2. The in silico toxicity prediction was performed from the best model obtained through the optimization of the FASTA query peptide. This prediction study revealed that BPP-BrachyNH2 induced high predicted LD50 values for both humans and rats, and then is well-tolerated in the recommended range. The MTT assay was applied for the in vitro cytotoxic evaluation in murine macrophages. In this assay, a decrease of cell viability was not observed. The in vivo acute toxicological study was performed after the intraperitoneal administration of BPP-BrachyNH2 at doses of 5 and 50 mg/kg. After intraperitoneal administration, no death, alterations in behavioral parameters or weight gain curve was observed, as well as none in the serum biochemical parameters, and gross pathological and histopathological analyses. These observations demonstrates an acceptable safety profile for BPP-BrachyNH2, leading towards further studies focused on investigation of pharmacological and therapeutical applications for this peptide.